TVA-Based Assessment of Visual Attention Using Line-Drawings of Fruits and Vegetables - Wang, Tianlu; Gillebert, Celine R. (Frontiers in Psychology, 2018)
Visuospatial attention and short-term memory allow us to prioritize, select, and briefly maintain part of the visual information that reaches our senses. These cognitive abilities are quantitatively accounted for by Bundesen’s theory of visual attention (TVA; Bundesen, 1990). Previous studies have suggested that TVA-based assessments are sensitive to inter-individual differences in spatial bias, visual short-term memory capacity, top-down control, and processing speed in healthy volunteers as well as in patients with various neurological and psychiatric conditions. However, most neuropsychological assessments of attention and executive functions, including TVA-based assessment, make use of alphanumeric stimuli and/or are performed verbally, which can pose difficulties for individuals that have troubles processing letters or numbers. Here we examined the reliability of TVA-based assessments when stimuli are used that are not alphanumeric, but instead based on line-drawings of fruits and vegetables. We compared five TVA parameters quantifying the aforementioned cognitive abilities, obtained by modelling accuracy data on a whole/partial report paradigm using conventional alphabet stimuli versus the food stimuli. Significant correlations were found for all TVA parameters, indicating a high parallel-form reliability. Split-half correlations assessing internal reliability, and correlations between predicted and observed data assessing goodness-of-fit were both significant. Our results provide an indication that line-drawings of fruits and vegetables can be used for a reliable assessment of attention and short-term memory.